Non-Persistence and Non-Adherence of Patients with Type 2 Diabetes Mellitus in Therapy with GLP-1 Receptor Agonists: A Retrospective Analysis. Issue 1 (March 2016) - Wilke, Thomas; Mueller, Sabrina; Groth, Antje; Berg, Bjoern; Fuchs, Andreas; Sikirica, Mirko; Logie, John; Martin, Alan; Maywald, Ulf
Abstract Introduction Our main aim was to assess the level of persistence and adherence to therapy with glucagon-like peptide-1 (GLP-1) receptor agonists in type 2 diabetes mellitus (T2DM) patients in the United Kingdom (UK) and Germany, also by comparing once- (OD) with twice-a-day (BID) therapy. Methods We used two large retrospective datasets: a German claims dataset and the UK General Practitioner (GP)-based Clinical Practice Research Datalink (CPRD) dataset (2010–2012). All continuously insured T2DM patients with at least one outpatient/inpatient T2DM diagnosis were observed starting with the first prescription of a GLP-1 receptor agonist. Non-persistence (NP) was defined as treatment gap >90 days. Non-adherence (NA) was defined as medication possession ratio <80%, calculated during a period in which a patient continued therapy (no treatment gap >90 days) only. Results In the UK sample, 1905 T2DM patients started a treatment with GLP-1 receptor agonists (mean age: 55.5 years, 47.2% female). In the German sample, 1627 T2DM patients started a treatment with GLP-1 receptor agonists (mean age: 56.6 years, 51.4% female). Percentage of NP patients after 12 months was 29.5% in the UK and 36.4% in the German sample. In both countries, a BID treatment was associated with a higher probability to discontinue a treatment with GLP-1 receptor agonists earlier than an OD treatment (hazard ratio [HR] = 1.431 in UK and HR = 1.314 in Germany). The percentages of patients considered NA were 20.2%/20.0%/20.5% (all/OD/BID) for the UK sample, and 19.9%/19.2%/21.8% (all/OD/BID) for the German sample. Conclusion NP and NA to treatment with GLP-1 receptor agonists in both UK and Germany appear to be similar. Persistence to OD treatment is higher than to BID treatment in both the UK and Germany.